Hound of the sea : wild man, wild waves, wild wisdom - McNamara, Garrett, 1967-; Karbo, Karen (HarperCollins Publishers, 2016)
In this memoir, "world record-holding and controversial Big Wave surfer Garrett McNamara chronicles his emotional quest to ride the most formidable waves on earth"--Amazon.com.